Proposed treatment algorithms for dogs with chronic bronchitis associated with irreversible airway changes: bronchiectasis and/or bronchomalacia - Lyssens, Aurélie; Roels, Elodie; Clercx, Cécile; Billen, Frédéric (Frontiers in Veterinary Science, 2025)
Chronic bronchitis (CB) in dogs involves persistent inflammation of the bronchial walls and excessive mucus production within the airways, with or without bronchial infection, and may lead to degenerative airway changes such as bronchiectasis (BE) and bronchomalacia (BM). Standardized treatment protocols for CB with concurrent BE and/or BM (BEBM) are lacking. This article proposes a therapeutic approach for dogs with CB and BEBM, based on veterinary literature and relevant human medical data. Two treatment algorithms are outlined, depending on the presence or absence of cytological evidence of bacterial infection in bronchoalveolar lavage fluid (BALF) and/or bronchial brush samples. For cases with suspected infection, indicated by intracellular bacteria on cytology, first-line therapy with oral doxycycline is recommended pending BALF culture and quantitative polymerase chain reaction (qPCR) results. If warranted, antibiotic therapy should be escalated stepwise after culture/qPCR confirmation, in accordance with antimicrobial stewardship principles. In non-infectious inflammatory cases, inhaled glucocorticoids are advised as first-line therapy and may also be used in infectious cases unresponsive to antibiotics alone. Mucoactive agents and cough suppressants are not recommended in the initial protocol but may be considered as adjunctive, symptom-targeted treatments on a case-by-case basis, avoiding unnecessary or unsupported interventions. These proposed algorithms are not intended as definitive clinical guidelines, but as a starting point for discussion and future validation. They emphasize rational and prudent use of antibiotics, alone or alongside anti-inflammatory therapy, to improve patient outcomes while minimizing antimicrobial resistance risks. Further research is needed to assess the long-term efficacy of this approach.